Comunicação e consumo de cultura fast-food: uma experiência Giraffas na praça de alimentação - Koutsantonis, Marina Pechlivanis (2008)
The purpose of this research is to investigate the communication and consume relations that are established in the restaurants of the Giraffas fast food network in food courts of shopping centers, meaningful meeting and socialization points of contemporaneity. Conceptually, the articulation among authors like Walter Benjamin, Roger Silverstone, Michel Maffesoli e Massimo Canevacci, building the experience of the fast-food culture. Methodologically, the view experience, allowing the analysis of different opinions about the communication impacts of the Giraffas network: the “geography” of the food court, the “ethnography” of the consuming practice and the “biography” of the consumer. For the corpus structure of the research, the West Plaza and Frei Caneca shopping centers, in São Paulo, selected by its geographical proximity (8 kilometers) and distance of cultural consumption.